The Life and Legend of the Sultan Saladin - Phillips, Jonathan, (Jonathan P.) (London : Vintage, 2020)
When Saladin recaptured Jerusalem from the Crusaders in 1187, returning the Holy City to Islamic rule for the first time in almost ninety years, he sent shockwaves throughout Christian Europe and the Muslim Near East that reverberate today. It was the culmination of a supremely exciting life, fraught with challenges but blessed occasionally with marvellous good fortune. Born into a significant Kurdish family in northern Iraq, Saladin shot to power far way in Egypt under the tutelage of his uncle. Over two decades, this warrior and diplomat worked tirelessly to build an immense empire that stretched from North Africa to Western Iraq. His even greater achievement was political uniting this turbulent coalition of people from a bewildering variety of religious and ethnic backgrounds behind his assault on the Holy Lands. And yet the capturing of Jerusalem was by no means the end of Saladin's epic and confounding story. Drawing primarily on Arabic as well as European sources, this is the most comprehensive account yet written not just of the man but of the legend to which he gave birth, describing vividly the relentless action of his life and then tracing its aftermath through culture and politics all the way to the present.
Includes index
Keywords: Saladin, Sultan of Egypt and Syria, -- 1137-1193; Crusades -- Third, 1137-1193; Egypt -- Kings and rulers -- Biography; Syria -- Kings and rulers -- Biography